A Lipid-Accumulating Alga Maintains Growth in Outdoor, Alkaliphilic Raceway Pond with Mixed Microbial Communities - Bell, Tisza A. S.; Prithiviraj, Bharath; Wahlen, Brad D.; Fields, Matthew W.; Peyton, Brent M. (Frontiers in Microbiology, 2016)
Algal biofuels and valuable co-products are being produced in both open and closed cultivation systems. Growing algae in open pond systems may be a more economical alternative, but this approach allows environmental microorganisms to colonize the pond and potentially infect or outcompete the algal “crop”. In this study, we monitored the microbial community of an outdoor, open raceway pond inoculated with a high lipid-producing alkaliphilic alga, Chlorella vulgaris BA050. The strain C. vulgaris BA050 was previously isolated from Soap Lake, Washington, a system characterized by a high pH (approximately 9.8). An outdoor raceway pond (200L) was inoculated with C. vulgaris and monitored for ten days and then the culture was transferred to a 2,000L raceway pond and cultivated for an additional six days. Community DNA samples were collected over the 16-day period in conjunction with water chemistry analyses and cell counts. Universal primers for the SSU rRNA gene sequences for Eukarya, Bacteria, and Archaea were used for barcoded pyrosequence determination. The environmental parameters that most closely correlated with C. vulgaris abundance were pH and phosphate. Community analyses indicated that the pond system remained dominated by the Chlorella population (93% of eukaryotic sequences), but was also colonized by other microorganisms. Bacterial sequence diversity increased over time while archaeal sequence diversity declined over the same time period. Using SparCC co-occurrence network analysis, a positive correlation was observed between C. vulgaris and Pseudomonas sp. throughout the experiment, which may suggest a symbiotic relationship between the two organisms. The putative relationship coupled with high pH may have contributed to the success of C. vulgaris. The characterization of the microbial community dynamics of an alkaliphilic open pond system provides significant insight into open pond systems that could be used to control photoautotrophic biomass productivity in an open, non-sterile environment.